Atherosclerosis as Mitochondriopathy: Repositioning the Disease to Help Finding New Therapies - Shemiakova, Taisiia; Ivanova, Ekaterina; Wu, Wei-Kai; Kirichenko, Tatiana V.; Starodubova, Antonina V.; Orekhov, Alexander N. (Frontiers in Cardiovascular Medicine, 2021)
Atherosclerosis is a complex pathology that involves both metabolic dysfunction and chronic inflammatory process. During the last decade, a considerable progress was achieved in describing the pathophysiological features of atherosclerosis and developing approaches that target the abnormal lipid metabolism and chronic inflammation. However, the early events in the arterial wall that initiate the disease development still remain obscure. Finding effective therapeutic targets in these early processes would allow developing methods forof disease prevention and, possibly, atherosclerotic plaque regression. Currently, these early events are being actively studied by several research groups. One of such early events isof the processes that are being investigated is the development of mitochondrial dysfunction, which was demonstrated to be present in the affected areas of the arterial wall. Detection and characterization of mitochondrial dysfunction associated with several chronic human disorders was made possible by the improved methods of studying mitochondrial biology and detecting mitochondrial DNA (mtDNA) mutations. It was found to be involved in several key atherogenic processes, such as oxidative stress, chronic inflammation, and intracellular lipid ac-cumulation. Mitochondrial dysfunction can occur in all types of cells involved in the pathogenesis of atherosclerosis: monocytes and macrophages, smooth muscle cells, lymphocytes, and the endothelial cells. However, therapies that would specifically target the mitochondria to correct mitochondrial dysfunction and neutralize the defective organelles are still remain to be developed and characterized. The aim of this review is to outline the prospects for mitochondrial therapy forof atherosclerosis. We discuss mechanisms of mitochondria-mediated atherogenic processes, known mitochondria-targeting therapy strategies, and novel mitochondria-targeting drugs in the context of atherosclerosis.